Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

SVM classifier incorporating simultaneous noise reduction and feature selection: illustrative case examples - Kumar, R.; Jayaraman, Valadi K.; Kulkarni, B. D. (Pattern Recognition, 2005)
A hybrid technique involving symbolization of data to remove noise and use of conditional entropy minima to extract relevant and non-redundant features is proposed in conjunction with support vector machines to obtain more robust classification algorithm. The technique tested on three data sets shows improvements in classification efficiencies. (C) 2004 Pattern Recognition Society. Published by Elsevier Ltd. All rights reserved.
Keywords: classification; conditional entropy; SVM; symbolization

Synthesis and characterization of value added catalysts zeolite beta using environmentally detrimental flyash - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N.; Kumar, R. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Fly ash is a major byproduct of Thermal power plant, which makes a lot of pollution to the environment due to its fineness. When a large amount of fly ash is dumped in the places near to power plants, it mixes in all segment of environment like water, air as well as soil. Though it can be utilized for different useful purposes, due to the lack of technical knowledge about how and proper motivation, no progress has been made in its utilization. It has been demonstrated that the fly ash can be used for making a value added catalyst zeolite beta by using simple and low cost process. In the present paper it is demonstrated that the fly ash can be used as a source of silica and alumina in the synthesis of value added catalyst zeolite beta. Moreover, the influence of different silica sources such as tetraethylortho silicate, silica sol and fumed silica on the physiochemical characteristics of well crystallized zeolite beta was also studied. The detailed characterization was carried out by using powder XRD, (27)Al and (29)Si MAS NMR, chemical analysis and low temperature nitrogen adsorption. Based on the data obtained from various systems containing different silica source, fumed silica is found to be most efficient source materials and showed superiority in the uniformity of aluminum distribution and possesses higher surface area.

Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.

Photocatalytic mineralization of benzene over gold containing titania nanotubes: role of adsorbed water and nanosize gold crystallites - Awate, S. V.; Sahu, R. K.; Kadgaonkar, Mahesh D.; Kumar, R.; Gupta, N. M. (Catalysis Today, 2009)
Well aligned titania nanotubes, with surface area of similar to 150 m(2) g(-1) and average pore diameter of similar to 5 nm, have been synthesized by subjecting a mesoporous TiO(2) sample to alkaline treatment followed by calcination at different temperatures. Composite catalysts with gold particles dispersed in these nanotubes were also synthesized and their structural, morphological, optical and photocatalytic properties were examined. The catalytic activity of TiO(2) for UV-mediated photo-oxidation of benzene was found to be affected by several factors, such as the sample texture. presence of adsorbed water and gold crystallites. The overall conversion of benzene to form CO(2) followed a trend: Au/nanotube > TiO(2) nanotubes > mesoporous TiO(2). In situ IR spectroscopy revealed that the adsorption and reaction of benzene molecules gave rise to formation of certain phenolic species over TiO(2), while the temperature-programmed desorption (TPD) study showed that the Au/TiO(2) interfaces serve as distinct sites for the adsorption and activation of oxygen molecules. It is suggested that certain hydroxyl and oxygen ion radicals produced under UV-irradiation may promote the deep oxidation of surface phenolic species and phenoxyl (ArO center dot) type transient radicals. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene degradation; Gold containing; Photocatalyst; Role of adsorbed water; TiO(2) nanotubes; Transient species

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

An innovative approach to enhance methane hydrate formation kinetics with leucine for energy storage application - Veluswamy, H. P.; Kumar, A.; Kumar, R.; Linga, P. (Applied Energy, 2017)
Natural gas storage in dathrate hydrates or solidified natural gas (SNG) offers the safest, cleanest and the most compact mode of storage aided by the relative ease in natural gas (NG) recovery with minimal cost compared to known conventional methods of NG storage. The stochastic nature of hydrate nucleation and the slow kinetics of hydrate growth are major challenges that needs to be addressed on the SNG production side. A deterministic and fast nucleation coupled with rapid crystallization kinetics would empower this beneficial technology for commercial application. We propose a hybrid combinatorial approach of methane hydrate formation utilizing the beneficial aspect of environmentally benign amino acid (leucine) as a kinetic promoter by combining stirred and unstirred reactor operation. This hybrid approach is simple, can easily be implemented and scaled-up to develop an economical SNG technology for efficient storage of natural gas on a large scale. Added benefits include the minimal energy requirement during hydrate growth resulting in overall cost reduction for SNG technology.

Effect of protonation and deprotonation on electron transfer mediated decay and interatomic coulombic decay - Kumar, R.; Vaval, N. (ChemPhysChem, 2023)
Electronically excited atoms or molecules in an environment are often subject to interatomic/intermolecular Coulombic decay (ICD) and/or electron transfer mediated decay (ETMD) mechanisms. A few of the numerous variables that can impact these non-radiative decay mechanisms include bond distance, the number of nearby atoms or molecules, and the polarisation effect. In this paper, we have studied the effect of protonation and deprotonation on the ionization potential (IP), double ionization potential (DIP), and lifetime (or decay width) of the temporary bound state in these non-radiative decay processes. We have chosen LiH-NH3 and LiH-H2O as test systems. The equation of motion coupled cluster singles and doubles method augmented by complex absorbing potential (CAP-EOM-CCSD) has been used in calculating the energetic position of the decaying state and the system's decay rate. Deprotonation of LiH-NH3/LiH-H2O either from the metal center (LiH) or from ammonia/water lowers the IP and DIP compared to the neutral systems. In contrast, protonation increases these quantities compared to neutral systems. The protonation closes the inner valence state relaxation channels for ICD/ETMD. For example, the decay of the O-2s/N-2s state stops in protonated systems (LiH2+-H2O, LiH2+-NH3, and LiH-NH4+). Our study also shows that the efficiency, i. e., the rate of ICD/ETMD, can be altered by protonation and deprotonation. It is expected to have implications for chemical and biological systems.